Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Customer Service Pada Bank Panin Cabang Utama Palmerah - Ridho Agustin; Dodi Prasada (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstrak. The purpose of this study was to determine the effect of leadership style and work environment on the performance of customer service employees at bank panin palmerah main branch. This research method uses quantitative methods with a sample size of 65 respondents, the data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, coefficient of determination analysis test, t test and f test. Based on the results of the t test, it is found that the leadership style (X1) has a positive and significant effect on the employee performance variable (Y). at Bank Panin Palmerah Main Branch. This is evidenced by the t value of 12.953> 1.998 and the significance value for the leadership style variable (X1) of 0.000 <0.05. Based on the results of the t test, the t value obtained for the work environment (X2) has a positive and significant effect on the employee performance variable (Y). at Bank Panin Palmerah Main Branch. Evidenced by the t value of 14.658> 1.998 and a significance value of 0.000 <0.05. Based on the results of the f test, the calculated f value of leadership style (X1) and work environment (X2) simultaneously has a positive and significant effect on employee performance (Y). at Bank Panin Palmerah Main Branch. Evidenced by the calculated F value of 125.007> 3.15 and a significance value of 0.000 <0.05. Keywords: Leadership Style, Work Environment, Employee Performance.